Effect of a COVID-19 on Social, Psychological, Economic and Health Conditions in Libya - Elgimati, Yousef; Alrasheed, Ahmed; Mohamed Bashir, Abdalla (Journal of Applied Science, Engineering, Technology, and Education, 2021)
The purpose of this paper was to measure the effect of a COVID-19 on social, psychological, economic, and health conditions in Libyan society. This study was undertaken through a questionnaire survey using the Google Form survey questionnaires in order to collect the data. A random sampling method was used from 1st June to 15th July 2020by obtaining greater insight into the issue. A result of this study revealed that the COVID-19 had a different effect on four dimensions (social, psychological economic, and health conditions). The findings of the study indicate that there is a small positive effect on social, middle, and above middle positive effects on psychological and economic respectively and high positive effect on health conditions with various percentages in Libyan society. This has been one of the first academic studies on the COVID-19 on social, psychological, economic, and health conditions addressed the Libyan society. Arguably, many of the areas covered in this study warrant more specific and in-depth investigation. The researchers hope that this paper will be beneficial to both Libyan people and the government in improving and developing the social aspects to avoid spreading COVID-19 in the future.